Toward a genome-based treatment landscape for renal cell carcinoma. (October 2019) - Massari, Francesco; Di Nunno, Vincenzo; Santoni, Matteo; Gatto, Lidia; Caserta, Claudia; Morelli, Franco; Zafarana, Elena; Carrozza, Francesco; Mosca, Alessandra; Mollica, Veronica; Iacovelli, Roberto; Sabbatini, Roberto; et al.
Highlights: Renal cell carcinoma is characterized by different genomic alterations and and variable mutations acquired in later phase of disease. Genomic alteration profile reflects tumor escapes from different external pressure. Metabolic, genomic and immune treatment related external pressure might influence mutations development in RCC. Better knowledge of RCC genomic landscape may lead to development of new tailored treatment for an accurate patients' selection. Abstract: Knowledge about molecular mechanisms driving development and progression of renal cell carcinoma has been elucidated by different studies. In few years we discovered a large difference between genomic landscapes of clear cell and non-clear cell carcinoma. Moreover, tumor heterogeneity and different acquisition of gene mutations during tumor progression are issues of particular interest. In this review we focalized our attention on principal genomic alterations identified among RCC subtypes. Acquired gene mutations may be an adaptive response to several external pressure including metabolic, treatment, genomic and immune-related external pressure. Thus we correlated and discussed principal genomic alterations adopted by tumor to escape from each external pressures. The aim of the present work is to summarize current knowledge about genomic alterations in RCC with special interest of treatment strategies tailored on the basis of disease mutations assessment.